An Impact Evaluation of New Normal Education for Building Student’s Superior Character - Sanggam Pardede; Dearlina Sinaga; Suryani Manurung (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study aimed to describe the impact of implementing a new normal education on students during the covid-19 pandemic. This research was qualitative research with a theoretical process evaluation approach. The study informants consisted of 3 groups namely 7 key informants, 15 main informants, and 10 supporting informants. Primary data was obtained from key and main informants through interviews and analyzed with the stage of the Miles model. The quality and validity of data used triangulation techniques by conducting in-depth interviews, and cross-testing through observations in the field, confirming through supporting informants and other sources. The study results showed: the implementation of a new normal education at UHN was carried out well and effectively, aspects of changes in academic and operational were carried out well and on target, aspect of changes in financing was carried out well, aspects of changes in facilities and infrastructure were carried out well, students could implement superior character through the fulfilment of creative, critical, communicative, collaborative and compassionate, and the impact of implementing new normal education for building superior character was carried out well. The results of the research suggested that in the future it needs analysis about space for students on campus to be able to realize their competencies related to learning achieved in each period, space to develop their local culture on campus, and space to transform their personalities in societies.